Acotiamide affects antral motility, but has no effect on fundic motility, gastric emptying or symptom perception in healthy participants. Issue 4 (20th January 2019) - Masuy, Imke; Tack, Jan; Verbeke, Kristin; Carbone, Florencia
Abstract: Background: Acotiamide, a prokinetic agent was shown to be efficacious in the treatment of functional dyspepsia (FD). The exact mechanism of action is incompletely elucidated. Methods: This randomized, placebo‐controlled, cross‐over study aimed to examine the effect of acotiamide on gastric motility, measured as intragastric pressure, gastric emptying (GE) rate and gastrointestinal (GI) symptom perception in healthy volunteers (HVs). Participants were treated with acotiamide (100 mg tid) and placebo for 3 weeks, separated by a 1‐week washout period. A daily symptom diary was collected during both treatments. At the end of each treatment period, GE rate and gastric motility were assessed with a 13 C‐octanoic acid breath test and high‐resolution manometry during nutrient infusion, respectively. GI symptom levels were scored during high‐resolution manometry. Data were analyzed using mixed models. The study was registered as NCT03402984. Key Results: Twenty HVs (10 female, 25 ± 4.1 years, 22.58 ± 2.73 kg/m 2 ) participated in the study. There was no difference in GE half time between both treatments ( P = 0.92). Acotiamide had no effect on fundic pressures before and after nutrient infusion ( P = 0.91). However, postprandial antral pressures remained significantly lower compared to placebo ( P = 0.015). There was no significant difference in hunger, satiation and GI symptoms scores assessed during IGP measurement and by the daily diary ( P > 0.12 for all). Conclusion: Acotiamide is associated with lower antral pressures after nutrient intake, whereas it has no effect on fundic pressures, GE rate and symptom perceptions in HVs. Studies in FD need to elucidate whether lower antral pressures induced by acotiamide underlie postprandial symptom improvement in FD. Abstract : Acotiamide, a novel prokinetic agent, reduced antral pressures in healthy controls after 3 weeks of treatment compared to placebo. It does not influence fundic pressures or gastric emptying time.